Analysis of Selection and Performance of Public Transport Mode In Tarakan City - Ing Daud Nawir; Muhammad Djaya Bakri; Iif Ahmad Syarif (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The problems of passenger transportation (TAP) in Tarakan City are multi-dimensional, such as, fares and routes that are less organized and uneven, inconvenience and less secure, excess passengers during peak hours and vice versa, condition of operator systems, increased pollution and noise and the number of accidents and traffic violations, and driver behavior. In short, the root of the problem is the incompatibility between the Regional Spatial Plan (RTRW) for the city of Tarakan and the TAP. This study aims to assess the performance of passenger transportation based on descriptive statistical methods to: see the demand for population movement; route performance and transport operations; and the performance of transportation infrastructure, as well as the level of road service in the form of the ratio of volume per road segment capacity. The results achieved found that the existing performance of TAP in Tarakan City was relatively not optimal, the level of main road service on secondary roads because the increase in vehicle volume was significantly influenced by the high population movement, land use, level of transportation service, transportation comfort, load factor, and road conditions.